How healthcare professionals overcome distance when collaborating with smart robots - Niehaus, Florian; Schank , Christoph; Schiavone, Francesco (Universität Vechta, 2025)
Smart robotic systems continue to make their way from industrial contexts to social applications. That shift necessitates further insights into interactions between human teams/team members and smart robots. These interactions have different patterns than interactions in strictly human teams. This study examines surgical teams and their interactions with the endoscopic surgical system (ESS) ‘da Vinci’ as a concrete implementation case. Its focus is the growing distance between team members upon introduction of the ESS robot. We follow a qualitative approach, based on semi-structured expert interviews with nine physicians of diverse fields of expertise and levels of experience with the ESS robot. Our findings show that surgeries with da Vinci bring about certain improvements as well as obstacles. Those can be grouped into physical, visual and coordinative dimensions. The main obstacles seem to be increased physical and mental distance between the ‘concertmaster role’ (i.e., the surgeon) and ‘ensemble roles’ (i.e., the rest of the surgery team). Surgery teams overcome these by applying visual and informational cues. We strengthen existing literature concerning the established physical distance and add the notion of mental distance in ESS-assisted surgeries. We suggest that surgery teams overcome physical and mental distance through visual and informational cues. Furthermore, we find that certain roles within a team get enriched, trimmed, or redesigned. Developers can utilize our findings to improve ESS robots. Medical and general management staff can use our findings for the improvement of team composition and governance, as well as process optimization and coordination, especially in human-robot teams.
Keywords: Robot; Da Vinci; Healthcare; Artificial intelligence; Interactions; Qualitative research; Technik, Medizin, angewandte Wissenschaften::610 Medizin und Gesundheit